Colonialism and Modern social theory - Bhambra, Gurminder K.; Holmwood, John (Medford Polity press, 2021)
Modern society emerged in the context of European colonialism and empire. So, too, did a distinctively modern social theory, laying the basis for most social theorizing ever since. Yet colonialism and empire are absent from the conceptual understandings of modern society, which are organized instead around ideas of nation state and capitalist economy. Gurminder K. Bhambra and John Holmwood address this absence by examining the role of colonialism in the development of modern society and the legacies it has bequeathed.
Keywords: Sociology philosophy; Politics and government; Europe colonies historiography